A New Gravitational Radiation from General Relativity (Journal of Nepal Physical Society, 2023)
Actual cosmological and galactic data is showing the possible existence of a non-visible gravitational mass. This mass has been called dark matter, and researchers are looking for an explanation of its physical nature. A new solution to Einstein’s general relativity equations is introduced here. This new solution assumes that gravity has density and can produce pressure as any other known field does. Our hypothesis does not create any mathematical contradiction with anything that is known and points to the conclusion that dark matter is a non-linear manifestation of the gravitational field.